Holographic Interferometer for the Study of Phase Media, Which Has Four Output Channels of Different Sensitivity - Yusupzhan Kh. Ismanov; Nasipbek K. Dzhamankyzov (International Journal of Optics)
Computer simulation of the interferometer combining properties of low-sensitive Talbot interferometer and high-sensitive holographic interferometer is considered. The interferometer has four output channels having different sensitivity. Channel sensibility can be varied by means of spatial filtration. The base of the interferometer is the holographic Talbot effect. The efficiency of this interferometer was verified by computer simulation method. Some results of the computer simulation are presented in the article. These results were compared with results obtained in optical experiments under the same conditions. A wide range of sensitivity of the interferometer makes it possible to use the interferometer to study complex phase objects, primarily dynamic media.